2009
DOI: 10.1103/physrevc.80.025207
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical coupled-channels analysis ofH1(e,eπ)

Abstract: We have performed a dynamical coupled-channels analysis of available p(e, e ′ π)N data in the region of W ≤ 1.6 GeV and Q 2 ≤ 1.45 (GeV/c) 2 . The channels included are γ * N , πN , ηN , and ππN which has π∆, ρN , and σN components. With the hadronic parameters of the model determined in our previous investigations of πN → πN, ππN reactions, we have found that the available data in the considered W ≤ 1.6 GeV region can be fitted well by only adjusting the bare γ * N → N * helicity amplitudes for the lowest N *… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
113
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(124 citation statements)
references
References 21 publications
10
113
1
Order By: Relevance
“…It is the chiral partner (J P = 1 2 − ) of the nucleon, and has strong decay channels for both πN and ηN. It has been suggested that N * (1535) can be dynamically generated as a KΣ quasi-bound state [5,6,7]. But it was also argued that pure valence quark effects are important to explain its electromagnetic structure [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the chiral partner (J P = 1 2 − ) of the nucleon, and has strong decay channels for both πN and ηN. It has been suggested that N * (1535) can be dynamically generated as a KΣ quasi-bound state [5,6,7]. But it was also argued that pure valence quark effects are important to explain its electromagnetic structure [6].…”
Section: Introductionmentioning
confidence: 99%
“…The N * (1535) spin state can have P-states in the relative quark-diquark configuration and/or in the diquark system. Assuming that the core spin 1/2 state is dominant [4] and a point-like diquark (no internal P-states), one can represent the N * (1535) wave function as 2 compared with the data and an estimate for the quark core contributions from EBAC [7]. Data are from Refs.…”
Section: Introductionmentioning
confidence: 99%
“…(Right panel): The form factors without pion-cloud (πN-loop) contribution. The results are from the current ANL-Osaka DCC analysis (red circles), our previous analysis [28,29] (green diamonds), and the SatoLee model [17] (blue dashed curve).…”
Section: Discussionmentioning
confidence: 99%
“…The N * and ∆ * baryons are the system of very broad and highly overlapping resonances, and this requires close cooperative works between the experiments and the theoretical analyses with coupled-channels approaches to accomplish a reliable extraction The full form factors from the current ANL-Osaka DCC analysis (red filled circles), our previous analysis [28,29] (green filled diamonds), and the Sato-Lee model [17] (blue solid curve). The red dashed curve is the meson-cloud contribution from the current ANL-Osaka DCC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, the reaction amplitudes T α,β (p, p ′ ; E) are calculated from the following coupled-channels integral equations, [3] and πN → ηN [4] up to W = 2 GeV, and γN → πN [5] and N(e, e ′ π)N [6] up to W = 1.6 GeV. Then, the model was applied to πN → ππN [7] and γN → ππN [8] to predict cross sections and examine consistency of the coupled-channels framework.…”
Section: Introductionmentioning
confidence: 99%